Associação da ocorrência de cianobactérias às variações de qualidade do efluente na lagoa de estabilização de Santa Eudóxia – São Carlos, SP e suas interferências no corpo receptor - Morales, Fernanda Igual (2015)
Wastewater stabilization ponds are an efficient method of decomposition organic matter in sewage treatment. Both biotic factors such as abiotic act in the ponds. Cyanobacteria are one of biotic factors of great importance to the process of sewage purification. Lot of nutrients can can result in high density cyanobacteria, characterized as eutrophication. These can release cyanotoxins that can harm health human and animal when in contact with them. Physical and chemical parameters are associated with both the presence of cyanobacteria and with the quality of the receiving body and allows evaluating compliance or not the standards required by legislation. Correlate the cyanobacteria density with the physical and chemical parameters and evaluate the receiving body in relation to the released effluent, were the objectives of this work. Quantitative and qualitative analysis of cyanobacteria were realized, and analyzes of the physico-chemical parameters according to Hach manual, and statistical analysis (regression analysis). The phosphorus and nitrogen analyzes have values close to those found in the literature. But phosphorus values downstream demonstrate inadequacy with the rules. The temperature in the pond is higher than the river, characterized by biochemical reactions that take place in this environment. The dissolved oxygen concentration was within the standards and remained in relation to previous studies. The pH and turbidity also attended the law. It has been found through mathematical model, which was thermal stratification in most months in the pond, with the pond in complete mixing in only four months. Statistical analysis showed a positive correlation between cyanobacteria and total nitrogen concentration, but a negative correlation with the effluent temperature. About the cyanobacteria in the pond the main genera found were Merismopedia, Oscillatoria and Pseudanabaena and in the river both upstream as downstream were Microcystis, Pseudanabaena and Limnothrix, indicating the toxic potential of these individuals in the water. The cyanobacteria values in the river downstream mainly, exceeded the value limit of the legislation. In general, some parameters exceeded the limits, but not damaged strongly the quality of the receiving body.